Thermal Management System of an Electric Vertical Take-off and Landing Flying Vehicle for Future Urban Air Mobility Application - Chen Yiqun; Wu Jianghong; Yang Huaiyu (Zhileng xuebao, 2025)
An electric vertical take-off and landing flying vehicle (eVTOL) is a potential technology for future urban air mobility. A major challenge for thermal management systems is the high cooling requirement and the variable application scenarios. To overcome this challenge, a multi-scene eVTOL-integrated thermal management system was developed. In this study, an eVTOL thermal management simulation platform based on Amesim simulation software was developed to investigate the effects of flight conditions on thermal management and range. The simulation results show that increasing the cruise altitude can reduce the thermal management energy consumption when the ground temperature is high. The maximum reduction of energy consumption for thermal management energy is 4 kW when the cruising temperature ranges from 10 ℃ to 26 ℃. When the hovering rescue duration is more than 150 s during the emergency rescue operation, the temperature difference inside the battery becomes too pronounced. A reduced payload improves the range, with the unloaded range being 1.33 times greater than the fully loaded range.